Robust angle estimation method for noncircular targets in MIMO radar with mutual coupling - Xianpeng WANG; Yuehao GUO; Mengxing HUANG; Chong SHEN; Chunjie CAO; Wenlong FENG (Tongxin xuebao)
A robust angle estimation method for noncircular targets based on unitary tensor decomposition with mutual coupling in multiple-input multiple-output (MIMO) radar was proposed.Firstly,utilizing the banded symmetric Toeplitz structure of the mutual coupling matrix to eliminate the influence of unknown mutual coupling in tensor field.Then a special augmented tensor was constructed to capture the no circularity and its inherent tensor multidimensional structure of noncircular signals.And taking advantage of the centro-Hermitian characteristic of the augmented tensor to transform the sub-tensor into real-values tensor by the unitary transformation.Finally,the signal subspace estimation based on tensor was obtained by taking advantage of the higher-order singular value decomposition (HOSVD) technology,and then the direction-of-departure (DoD) and direction-of-arrival (DoA) estimation was obtained by utilizing the real-values subspace technology.Due to the consideration of both the noncircularity and multidimensional structure,the proposed algorithm has better recognition performance than the existing angle estimation methods.At the same time,the proposed algorithm only requires real-valued operations and has lower computational complexity.Simulation experiments verify the effectiveness and superiority of the proposed algorithm.